Arahan Penggunaan Lahan untuk Pengendalian Erosi Tanah di Sub-DAS Wuryantoro DTA Waduk Gajah Mungkur Wonogiri Jawa Tengah - Senawi Senawi (Jurnal Ilmu Kehutanan, 2009)
Recommendation of Land Use Allocation to Control Soil Erosion in Wuryantoro Sub-Watershed DTA Gajah Mungkur Reservoir, Wonogiri, Central JavaThe research aims to recommend optimum land use allocation that can control soil surface erosion in Wuryantoro sub-watershed. The research was done using land evaluation aproach to land unit and analyzed based on area function allocation, land capability classification, and erosion hazard rate. Optimization analysis on land use allocation was done statistically through linear program symplex method using QSB software.The results showed that actual land use caused actual soil surface erosion (A) of Wuryantoro subwatershed was higher that tolerable erosion (T) treshold. Optimization analysis recommends that to control actual soil surface erosion (A) to be lower that tolerable erosion (T) treshold, its is needed to convert all actual land uses of groves and croplands to forest. Actual land uses of production forests, community forests, irrigated farmlands, rainfeed farmlands, and residential could still be kept remain as they were.